2000
DOI: 10.1159/000051385
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Acid Suppression in Nonvariceal, Acute, Upper Gastrointestinal Bleeding

Abstract: Nonvariceal, upper gastrointestinal (GI) bleeding is a very common source of morbidity and mortality. The concept of ulcer clot dissolution being facilitated by a low gastric pH has allowed us to better understand the pathophysiology of nonvariceal upper GI bleeding. Placebo-controlled trials have shown the benefit of oral proton pump inhibitor administration in contrast to H2 receptor antagonists. Furthermore, our recent experience with intravenous proton pump inhibitors has reinforced these observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…Several randomized‐controlled trials on the effectiveness of the two drugs for preventing rebleeding after endoscopic haemostasis of haemorrhagic peptic ulcers are controversial: some reports state that PPIs are better 15 and others state that both treatments are the same 16 . Gastric pH affects blood coagulation and platelet aggregation at the site of bleeding 17 . It has been reported that pepsin is active below pH 5.0 and accelerate clot digestion 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized‐controlled trials on the effectiveness of the two drugs for preventing rebleeding after endoscopic haemostasis of haemorrhagic peptic ulcers are controversial: some reports state that PPIs are better 15 and others state that both treatments are the same 16 . Gastric pH affects blood coagulation and platelet aggregation at the site of bleeding 17 . It has been reported that pepsin is active below pH 5.0 and accelerate clot digestion 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature search of randomized trials and published reviews, [4][5][6][7][16][17][18][19][20][21][22][23][24][25][26] only two randomized studies fulfilled the pre-set selection criteria. 4,7 Others either did not allow for a precise estimate of the probability of re-bleeding 5,6 or included patients who did not have high-risk ulcer lesions.…”
Section: Probability Estimatesmentioning
confidence: 99%
“…However, not all types of acid‐suppressive therapy have similar efficacy profiles. There is general agreement that proton pump inhibitors (PPI), e.g., pantoprazole and omeprazole, are more effective than H 2 ‐receptor antagonists for the treatment and prevention of UGI bleeding from severe gastric‐acid‐related disorders [1–4]. High‐dose parenteral PPIs have also recently been introduced to provide rapid acid suppression when the patient's medical condition precludes giving oral formulations [1].…”
Section: Introductionmentioning
confidence: 99%